2013
DOI: 10.1177/0148607113501556
|View full text |Cite
|
Sign up to set email alerts
|

Complex Dietary Protein Improves Growth Through a Complex Mechanism of Intestinal Peptide Absorption and Protein Digestion

Abstract: A complex protein diet stimulates in an altered pattern of intestinal peptide transporter expression and intestinal proteolytic activity that results in improved growth compared with a diet of elemental amino acids. This improved growth appears to be the result of increased efficiency of a smaller number of enterocytes. These data might be useful in targeting intestinal rehabilitation therapies for short bowel syndrome and other risk factors for intestinal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Previous studies have reported that the transformation among Arg, citrulline (Cit), and Orn can be regulated with the addition of Gln. The close association of Gln and Arg in epithelial metabolism (Watford, ), as well as the regulation of Arg utilization by Gln in porcine small‐intestinal bacteria, suggests that an analogous metabolic pathway is shared in the production of these two AAs (Hansen, Ashley, & Chung, ). These findings intimate that Gln accomplishes the metabolism of the Arg family through bacterial mediation in the intestine (Blachier et al., ; Corpeleijn et al., ).…”
Section: Glutamine Gut Microbiota and Immunitymentioning
confidence: 99%
“…Previous studies have reported that the transformation among Arg, citrulline (Cit), and Orn can be regulated with the addition of Gln. The close association of Gln and Arg in epithelial metabolism (Watford, ), as well as the regulation of Arg utilization by Gln in porcine small‐intestinal bacteria, suggests that an analogous metabolic pathway is shared in the production of these two AAs (Hansen, Ashley, & Chung, ). These findings intimate that Gln accomplishes the metabolism of the Arg family through bacterial mediation in the intestine (Blachier et al., ; Corpeleijn et al., ).…”
Section: Glutamine Gut Microbiota and Immunitymentioning
confidence: 99%
“…This observation confirms previous suggestions that structural and functional adaptation may be separate, uncoupled responses. 35 This is supported by the fact that other animal experiments have shown dietary protein improves growth independent of increased intestinal peptide or amino acid transporter expression 14 .…”
Section: Discussionmentioning
confidence: 91%
“…Many proposed modified diets with different proportions of fat, 12,13 carbohydrates, and protein 14,15 have been used in clinical trials in an attempt to wean patients off of TPN. Most recently, a randomized control trial tested the efficacy of administering enteral high-fat diet to premature infants with an enterostomy.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the statement that the diet of patients with a chronic liver disease must contain appropriate proteins to avoid a severe protein deficiency (Sanchez and Aranda-Michel, 2006), branched chain amino acids which enable fast recovery of muscle tissue are frequently applied. However, Hansen et al (2015) have recently shown that the diet with complex proteins stimulates proteolytic activity of enterocytes and results in improved growth.…”
Section: Figure 2 Average Daily Macronutrients Intake For Patients Wmentioning
confidence: 99%